As formas simbólicas espaciais e a dinâmica da centralidade em Vitória : um esforço de análise - Zippinotti, Daniel Pitzer (2014)
The present labour approaches, on the renewed cultural geography perspective's, the tematic of symbolic forms on the urban space, having as problematization the case study from the most representatives spatials symbolic forms of the centrality in the Central Area of Vitória (ES) The interest about the theme is associated to the relatively recent scenario in which the Central Area of Vitória, mainly in the two last decades from the XX century, starts suffering with an intense process of descentralization presenting as some effects of this dinamic not only the appearing of secundary nucleus of comercy and services far from the Central Area, but also exerts a elementary character in a phenomenon recognized as 'the central area crises'. However, if the scenario described above is too much recent, in opposite, durante the long period of urban space production of the capital capixaba in which the intern organization of the city was tributary, fundamentally, in the centralization process, the Vitória's downtown was the privileged locus of the materialization of the symbolic spatial forms tipically associated with inner urban centrality as buildings that are symbols from politic, legal and economic power, churches, the monuments, between another spatial symbolic forms. In this way, the dissertation pretends to investigate the advent of the descrentralization upon the spatial symbolic forms tipically associated to the Central Area of the capital capixaba, questioning in which measure these forms remained while signs of symbolic resistance to the meaning of the area, as also the nature of the casual requalifications of meanings to what they were eventually submitted.